Ocean acidification enhances the tolerance of dinoflagellate Prorocentrum donghaiense to nanoplastic-induced oxidative stress by modulating photosynthetic performance - Yue Zhu; Yue Zhu; Qingming Lin; Qingming Lin; Yao Yang; Yanmei Xia; Yanmei Xia; Huidi Cai; Huidi Cai; Xucong Feng; Xucong Feng; Rodrigo J. Gonçalves; et al. (Frontiers in Marine Science)
IntroductionThe impact of ocean acidification (OA) and nanoplastics (NPs) on harmful algal blooms (HAB) has emerged as a major global concern. However, the combined effects of OA and NPs on the HAB species are poorly understood.MethodsIn this study, dinoflagellate Prorocentrum donghaiense, a typical HAB species, was exposed to varying concentrations of NPs (108.15 ± 8.52 nm) (0, 5, 10, and 15 mg L−1) and CO2 (low CO2: 417 ppm, pH: 8.00 and high CO2: 1045 ppm, pH: 7.73) for seven days to investigate the combined effects of OA and NPs.Results and discussionThe findings revealed that NPs inhibited the growth of P. donghaiense by inducing oxidative stress, as indicated by elevated malondialdehyde (MDA) content and decreased carotenoid/chlorophyll-a ratio, even though photochemical efficiency (φP0, ψ0, and φE0), rETRmax and α were enhanced in response to NPs stress. However, OA promoted the growth and alleviated the adverse effects of NPs on P. donghaiense by increasing photochemical efficiency (φP0, ψ0, and φE0) and energy flux (RC/CS0, TR0/CS0, ET0/CS0) and enhancing the antioxidant ability (increased superoxide dismutase, and decreased MDA). P. donghaiense showed enhanced tolerance to NPs under simulated OA conditions. These findings enhance our knowledge of the HAB species response to NPs pollution under future OA scenarios.